(untitled) (Revista Electrónica REDINE, 2018)
This study is framed in a bibliographic documentary research, whose main objective was to characterize the academic performance of students of Psychology participants or not the pre-university course in 2012. The sample consisted of 32 graduates (6 men and 22 women) trainees and 49 pre-university graduates (39 women and 10 men) with no high school. A descriptive statistical analysis of the data obtained in the Experimental Academic Registry Dean of Arts and Humanities was used. To do this we proceeded to prioritize and interpret the results tabulated percentage and the respective statistics were calculated. This type of study led to the conclusion that student academic achievement of participants in university induction does not allow transcendent contrasts with the non-trainee group that academic event. That is, when making the comparison group averages, no significant differences to justify the development and implementation of these pre-university courses were detected. It was recommended that the authorities responsible for planning this type of event seek help improve generically contents and processes of pre-university inductions of future freshmen.